Perturbation of maternal gut microbiota in mice during a critical perinatal window influences early neurobehavioral outcomes in offspring. (15th May 2023) - Morel, Cassandre; Martinez Sanchez, Ines; Cherifi, Yamina; Chartrel, Nicolas; Diaz Heijtz, Rochellys
Abstract: The gut microbiota is increasingly recognized as a key environmental factor that shapes host development and physiology, including neural circuits formation and function. Concurrently, there has been growing concern that early-life antibiotic exposure may alter brain developmental trajectories, increasing the risk for neurodevelopmental disorders such as autism spectrum disorder (ASD). Here, we assessed whether perturbation of the maternal gut microbiota in mice during a narrow critical perinatal window (last week of pregnancy and first three postnatal days), induced by exposure to a commonly used broad-spectrum oral antibiotic (ampicillin), influences offspring neurobehavioral outcomes relevant to ASD. Our results demonstrate that neonatal offspring from antibiotic-treated dams display an altered pattern of ultrasonic communication, which was more pronounced in males. Moreover, juvenile male, but not female, offspring from antibiotic-treated dams showed reduced social motivation and social interaction, as well as context-dependent anxiety-like behavior. However, no changes were observed in locomotor or exploratory activity. This behavioral phenotype of exposed juvenile males was associated with reduced gene expression of the oxytocin receptor (OXTR) and several tight-junction proteins in the prefrontal cortex, a key region involved in the regulation of social and emotional behaviors, as well as a mild inflammatory response in the colon. Further, juvenile offspring from exposed dams also showed distinct alterations in several gut bacterial species, including, Lactobacillus murinus, and Parabacteroides goldsteinii. Overall, this study highlights the importance of the maternal microbiome in early-life, and how its perturbation by a widely used antibiotic could contribute to atypical social and emotional development of offspring in a sex-dependent manner. Graphical abstract: Image 1 Highlights: Perinatal antibiotic exposure has enduring effects on offspring gut microbiota. Early social communicative behaviors are influenced by perinatal antibiotic exposure. Effects on social-emotional behaviors occur in a sex- and context-dependent manner. Evidence of altered Oxtr gene expression and BBB integrity in the prefrontal cortex. Males are more sensitive than females to perinatal antibiotic exposure.